Reference Virtual Design Team (VDT) probabilities to Design Construction Project Organizations - Concha, Marcelo; Alarcón, Luis Fernando; Mourgues, Claudio (Revista de la Construcción. Journal of Construction, 2015)
This paper reports the results obtained from five virtual models of construction project organizations developed using the Virtual Design Team (VDT) method. The results were compared with the real project organization performance in each case and their probabilities inputs were calibrated to obtain benchmark reference inputs for future projects. The models were validated comparing their predictions with real results obtained in the projects and the predicted behavior of the organizations was subjected to the assessment and approval of technical experts of the companies in the study. The calibrated models obtained represent reality within appropriate margins given the variable nature of the problem, being able to predict the performance of projects with results generally less than 5% difference between the real performance and modeling results, achieving probabilities close to those from literature and well received by companies in the structured interview, with over 70% approval in the predicted factors covered. These results contribute to expand the uses of VDT methodology and to adapt this methodology to local companies, which enables to model organizations at the planning and design phase, achieving improvements in terms of cost, schedule and quality risks.